Arranjos de música popular brasileira no contexto modal: a construção da linha do contrabaixo - Maia, Claudio Marcelo Bezerra (2018)
The present has as object the arrangements of brazilian popular music in the modal context, particularly the bass line. The general objective is to discuss the construction of the double bass line in the development of arrangements for brazilian popular music in the modal context in order to offer greater freedom of creation/performance to the bassist. To this end, is organized into three main parts: 1) Literature review: discussion of references in printed and audiovisual material on double bass and MPB, especially those involving performance and modalism, available in portuguese language; 2) Selection and discussion of the material reviewed: two songs from the repertoire of MPB, which present the modalism and will serve as object to the arrangements; 3) Preparation of double bass lines in the modal context to be taken into account in arrangements.